2014
DOI: 10.5152/tpa.2014.1795
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties experienced during preparation and administration of oral drugs

Abstract: In our study, it was found that all nurses experienced difficulty in preparing and administering drugs. The problems experienced by the nurses and solution recommendations for these problems were reported to the hospital administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Nurses insist that negligence and errors in medication orders recorded by doctors is a starting point that leads to errors. In line with the current findings, researchers confirmed the impact of physician errors on nurses' medication errors (Valizadeh et al, 2008) and reported that medication errors had been made by the physicians that prescribed the drugs (Boztepe et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nurses insist that negligence and errors in medication orders recorded by doctors is a starting point that leads to errors. In line with the current findings, researchers confirmed the impact of physician errors on nurses' medication errors (Valizadeh et al, 2008) and reported that medication errors had been made by the physicians that prescribed the drugs (Boztepe et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly another researcher stated that administering oral medications in pediatric wards needs more time and nurses become fatigued (Boztepe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The data was collected using a data collection questionnaire based on the relevant literature [11,[25][26][27]. The data collection form included four sections (Additional file 1).…”
Section: Intervention (Questionnaire)mentioning
confidence: 99%
“…Regarding correct dosage, in this study we observed the partition of pills not previously grooved by the manufacturer (76.31%). A research conducted with 108 pediatric nurses of a university hospital in Turkey reinforces such findings, as it evaluated the preparation and administration of 406 oral drugs and identified that the process of parting the pills into appropriate doses was the difficulty most commonly reported by professionals (45.3%) (28) . Non-grooved industrialized pills are the most reliable way to obtain the desired concentration of the active ingredient, and the partition of such medications is a risk for the administration of doses that do not correspond to the prescribed dosage, which can compromise the effectiveness of the treatment (29) .…”
Section: Discussionmentioning
confidence: 89%